Phosphorylation of the Yeast Heat Shock Transcription Factor Is Implicated in Gene-Specific Activation Dependent on the Architecture of the Heat Shock Element - Hashikawa, Naoya (American Society for Microbiology, 2004)
Heat shock transcription factor (HSF) binds to the heat shock element (HSE) and regulates transcription, where the divergence of HSE architecture provides gene- and stress-specific responses. The phosphorylation state of HSF, regulated by stress, is involved in the activation and inactivation of the transcription activation function. A domain designated as CTM (C-terminal modulator) of the Saccharomyces cerevisiae HSF is required for the activation of genes containing atypical HSE but not typical HSE. Here, we demonstrate that CTM function is conserved among yeast HSFs and is necessary not only for HSE-specific activation but also for the hyperphosphorylation of HSF upon heat shock. Moreover, both transcription and phosphorylation defects due to CTM mutations were restored concomitantly by a set of intragenic suppressor mutations. Therefore, the hyperphosphorylation of HSF is correlated with the activation of genes with atypical HSE but is not involved in that of genes with typical HSE. The function of CTM was circumvented in an HSF derivative lacking CE2, a yeast-specific repression domain. Taken together, we suggest that CTM alleviates repression by CE2, which allows HSF to be heat-inducibly phosphorylated and presume that phosphorylation is a prerequisite for the activator function of HSF when it binds to an atypical HSE.